(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Modern approaches to improving the work of paramedics in patient care are one of the main aspects of the healthcare sector. In the modern world, medicine is developing rapidly, and the requirements for the quality of patient care are also increasing. In this regard, the issues of improving the professional skills of paramedics and effectively organizing their work remain relevant.